Active methodologies in medicine courses: an integrative review (Research, Society and Development, 2020)
The introduction of active teaching methodologies in the medical course was carried out with the aim of promoting the training of a humanized, interprofessional and general professional as one who has critical-reflective thinking and the ability to deal with more support with problem situations. The objective was to search the literature for studies that addressed the use of active methodologies in medical courses. Through electronic databases Google Scholar and Web of Science and in the Periodicals Portal of the Coordination for the Improvement of Higher Education Personnel (CAPES), the combinations of keywords were sought: Active Methodologies, Medicine, Teaching. 10 articles that met the studied theme were carefully analyzed, presenting as a result mostly positive aspects in the use of active methodologies, but still with aspects to improve according to the students, aiming to end paradigms rooted by the traditional method, so that there is total application of the concepts that this method brings. It is concluded that the current gradual scenario of changes between traditional methodologies for active methodologies continues to become in the future the only one to be used by medical courses.